Apoptosis of nurse cells at the late stages of oogenesis of Drosophila melanogaster. - Cavaliere, V.; Taddei, C.; Gargiulo, G. (Development genes and evolution, 1998)
In Drosophila a remarkable feature of oogenesis is the regression of the nurse cells after dumping their cytoplasmic contents into the oocyte. We have studied the nature of this process at the late stages of egg chamber development. In egg chambers DAPI staining shows highly condensed chromatin from stage 12 and TUNEL labelling shows DNA fragmentation up to stage 14. Gel electrophoresis of the end-labelled DNA, extracted from isolated egg chambers at the same stages of development, shows a ladder typical of apoptotic nuclei. This provides evidence that, during Drosophila oogenesis, the nurse cells undergo apoptosis. Apoptotic nuclei have also been detected in dumping-defective egg chambers, indicating that the cytoplasmic depletion of nurse cells is concurrent with but apparently not the cause of the process.